COVID-19 pandemic and vaccination rate in patients with psoriasis treated with biologics: a single center experience - Milčić, Danijela; Malinić, Marija; Ćirković, Andja; Krupniković, Doroteja; Milinković Srećković, Mirjana (Vojnosanitetski pregled, 2024)
Introduction: Psoriasis is a chronic, immune-mediated, genetically determined disease, presented with erythematous scaly plaques. Treatment includes conventional therapies and biologics. Coronavirus disease 2019 (COVID-19) raised widespread concern about the treatment of psoriasis, with immunosuppressive drugs, especially biologics. Even though there was no data on the efficacy and safety of COVID-19 vaccines in patients with psoriasis treated with biologics, the National Psoriasis Foundation recommends their use in these patients. Aim: The aim of this study was to evaluate the effect of vaccination and COVID-19 infection in patients with psoriasis treated by biologics and disease state. Materials and methods: A retrospective cohort study was conducted at the Clinic of Dermatovenereology, University Clinical Center of Serbia (UCCS) during the COVID-19 pandemic. Data was collected from medical documentation, all stored in the computer database – Heliant during the consecutive hospitalization of patients with psoriasis who received biologics. Results: A total of 181 patients with psoriasis were treated with two biologics (ustekinumab 61% and secukinumab 37%) and achieved significant improvement of psoriasis severity (PASI before 14.1 (0-50.5) and after 1.2 (0-49.7), p<0.001) and quality of life (DLQI before 15.0 (0-34) and after 0 (0-28)). Vaccine against COVID-19 infection received 53%, but only 20.4% received three doses. COVID-19 infection was reported in 34.5% of all patients, but 68% of them got infected before getting vaccinated. Therapy with biologics was delayed due to COVID-19 infection in 29% and 21% of them had exacerbation of psoriasis. Conclusion: Vaccination rate in patients with psoriasis receiving biologics was hardly 50%, and about a third of the patients had milder form of COVID-19 infection. The therapy with biologics was successful in patients with psoriasis, regardless of the interruption and worsening of the main disease in some patients due to COVID-19 infection for a short period.